The Effect of Maternal Hypertension Status on Stunting Incidence: A Systematic Review - Dwi Putri, Wanda Luthfiani; Ayu Anulus (Journal of Health Management, Administration and Public Health Policies, 2024)
Stunting is a serious problem that results in stunted growth and development in children under the age of five.  Children who are stunted have a high risk of being affected by pregnant women who have a history of hypertension. This study was to analyze the effect of maternal hypertension status on the incidence of stunting, using a systematic review approach technique. The articles used in this study are full-text articles with an observational study design (cross-sectional, cohort, and case control) published from 2014 to 2024. The independent variables include the level of maternal hypertension status, and the dependent variable is the incidence of stunting. Article data collection was carried out by searching for articles in the Google Scholar, PubMed, and Science Direct search databases. The results showed that mothers who experience hypertension during pregnancy have a higher risk of giving birth to children who experience stunting. This is because hypertension can interfere with fetal development and affect the physical growth of children after birth. Keywords: Hypertension, Pregnant mother, Stunting